A long shadow: Cultural capital, techno-capital and networking skills of college students. (May 2017) - Lee, Kyung Sun; Chen, Wenhong
Abstract: Networking skills are conventionally treated as a form of human capital shaped by individual attributes. In this study, we investigate the relationship between cultural capital, techno-capital and networking skills among college students. Based on a survey of a sample of college students, we identify that socialization into various cultural genres in an early age equips individuals with the cultural knowledge, attitude, and disposition to network skillfully. Second, we find that digital competency can contribute to networking skills. In particular, digital cultural production, in other words, actively engaging in creative online expression of one's cultural taste, is positively related to greater networking skills. Theoretical and practical implications are discussed. Highlights: This study examines the relationship between cultural capital, techno-capital and networking skills among college students. Techno-competency, or operational and critical digital literacy skills, is positively related to networking skills. Engaging in digital content production has a positive influence on networking skills among college students. Socialization into diverse cultural genres from an early age can contribute to networking skills among college students. This study points to a mechanism by which techno-capital may contribute to upward social mobility for disadvantaged students.